2015
DOI: 10.1007/s00134-014-3639-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-pathogen real-time PCR system adds benefit for my patients: yes

Abstract: Need for the diagnosis of bloodstream infectionsBloodstream infections (BSI) are a major cause of death [1] and it is accepted that initiating an effective antimicrobial therapy in severe sepsis reduces mortality in a timely manner [2, 3]. In the era of increasing resistance, knowing pathogen and antibiotic susceptibility is critical for initiating appropriate antimicrobials [4, 5]. Unfortunately, microbial documentation of severe infections leading to BSI is still often overlooked and recognized too late for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…It should be noted that in the previous studies, many cases were shown with positive molecular tests and BC-negative with clinical status showing signs of bloodstream infections [21, 22]. The cost-effectiveness of molecular direct testing in blood remains unknown [23]. …”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that in the previous studies, many cases were shown with positive molecular tests and BC-negative with clinical status showing signs of bloodstream infections [21, 22]. The cost-effectiveness of molecular direct testing in blood remains unknown [23]. …”
Section: Introductionmentioning
confidence: 99%
“…2011), involvement of fastidious, slow growing, anaerobic or viable but non culturable (VBNC) bacteria (Al‐Tuffyli and Shekhan 2012); antibiotic pretreatment (Loonen et al . 2014) and the presence of intracellular pathogens which are phagocytized or only present in an infectious focus (Cambau and Bauer 2015).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, blood cultures are less sensitive especially in the setting of recent exposure to antibiotics. Overall, blood cultures have only 70% specificity, and sensitivity *Correspondence: jarturpaiva@gmail.comis approximately 10% in suspected bacteremia, 30% in febrile neutropenia, 35% in severe sepsis, and 50% in septic shock [10]. Defining a true positive result for evaluating diagnostic tests for infection is challenging and may be best by a composite measure that includes clinical status and type and severity of infection.…”
mentioning
confidence: 99%